Application of the PjBL (Project Based Learning) Learning Model to Increase Creativity and Student Learning Outcomes on the Topic of the Solar System Class 7 - Yanuan Widiarani; Purwandari Purwandari; Umi Nurf Hasanah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
Abstract: The research focused on the variables of creativity and learning outcomes to determine their improvement in the classroom. The research method used is PTK which starts from the stages of planning, action, observation, and reflection. The subject of this research was carried out by 32 students in class VII. The research instrument to determine the increase in creativity is carried out by using a learning creativity questionnaire at the beginning and end of the activity, a diagnostic test and a posttest for learning outcomes in each cycle implementation process. This type of research action used the stages of pre-cycle, cycle 1, and cycle 2. The results of the research on student creativity in the pre-cycle were 18.75% of students having good creativity criteria, as many as 81.25% of students had fairly good creativity criteria. Then the research was carried out and the results of student creativity in postgraduate as much as 6.25% had very good creativity criteria, 53.11% had good creativity criteria, and 40.63% had pretty good creativity criteria. Student learning outcomes show that in the pre-cycle 37.50% of students complete, in cycle 1 as many as 81% of students complete, and in cycle 2 as much as 100% of students complete. It can be seen that student learning outcomes have increased.